Chief Complaints, Underlying Diagnoses, and Mortality in Adult, Non-trauma Emergency Department Visits: A Population-based, Multicenter Cohort Study - Michael Dan Arvig; Christian Backer Mogensen; Helene Skjøt-Arkil; Isik Somuncu Johansen; Flemming Schønning Rosenvinge; Annmarie Touborg Lassen (Western Journal of Emergency Medicine, 2022)
Introduction: Knowledge about the relationship between symptoms, diagnoses, and mortality in emergency department (ED) patients is essential for the emergency physician to optimize treatment, monitoring, and flow. In this study, we investigated the association between symptoms and discharge diagnoses; symptoms and mortality; and we then analyzed whether the association between symptoms and mortality was influenced by other risk factors. Methods: This was a population-based, multicenter cohort study of all non-trauma ED patients ≥18 years who presented at a hospital in the Region of Southern Denmark between January 1, 2016–March 20, 2018. We used multivariable logistic regression to examine the association between symptoms and mortality adjusted for other risk factors. Results: We included 223,612 ED visits with a median patient age of 63 and even distribution of females and males. The frequency of the chief complaints at presentation were as follows: non-specific symptoms (19%); abdominal pain (16%); dyspnea (12%); fever (8%); chest pain (8%); and neurologic complaints (7%). Discharge diagnoses were symptom-based (24%), observational (hospital visit for observation or examination, 17%), circulatory (12%), or respiratory (12%). The overall 30-day mortality was 3.5%, with 1.7% dead within 0–7 days and 1.8% within 8–30 days. The presenting symptom was associated with mortality at 0–7 days but not with mortality at 8–30 days. Patients whose charts were missing documentation of symptoms (adjusted odds ratio [aOR] 3.5) and dyspneic patients (aOR 2.4) had the highest mortality at 0–7 days across patients with different primary symptoms. Patients ≥80 years and patients with a higher degree of comorbidity had increased mortality from 0–7 days to 8–30 days (aOR from 24.0 to 42.7 and 1.9 to 2.8, respectively). Conclusion: Short-term mortality was more strongly associated with patient-related factors than with the primary presenting symptom at arrival to the hospital.